PENGARUH BUDAYA ORGANISASI, DAN KEPUASAN KERJA TERHADAP KOMITMEN ORGANISASIONAL (Survey pada Perum Perumnas Regional III Wilayah JABODETABEK 2018) - Imam Santoso (Aliansi : Jurnal Manajemen dan Bisnis, 2018)
This study aims to obtain information relating to the influence of organizational culture, and job satisfaction on Organizational Commitment. Research has been carried out using path analysis after all variables were entered into the correlation matrix. In this study, 300 employees of the third-level housing company in Jabotabek as a population were randomly selected as the analysis unit of 80 samples along with the four characteristics studied. The results showed that (1) organizational culture has a direct effect on organizational commitment, (2) organizational job satisfaction has a direct effect on employee work performance, (3) job satisfaction has a direct effect on organizational commitment. (4) Organizational culture has an indirect effect on organizational commitment through employee job satisfaction. The results of the study show that organizational culture, job satisfaction is an important determinant of employee work performance. Based on these findings it can be concluded that any changes or variations that occur in the organizational commitment of Perumnas employees have been influenced by organizational culture and job satisfaction. Therefore, organizational culture, and job satisfaction must be included in the strategic planning of human resource development in increasing the organizational commitment of Perumnas employees, but need to consider other variables needed to Organizational commitment is influenced by variations in organizational culture, and job satisfaction.